Crafting the plant root metabolome for improved microbe‐assisted stress resilience. Issue 6 (24th December 2021) - Hong, Yechun; Zhou, Qian; Hao, Yuqiong; Huang, Ancheng C.
Summary: Plants and microbes coinhabit the earth and have coevolved during environmental changes over time. Root metabolites are the key to mediating the dynamic association between plants and microbes, yet the underlying functions and mechanisms behind this remain largely illusive. Knowledge of metabolite‐mediated alteration of the root microbiota in response to environmental stress will open avenues for engineering root microbiotas for improved plant stress resistance and health. Here, we synthesize recent advances connecting environmental stresses, the root metabolome and microbiota, and propose integrated synthetic biology‐based strategies for tuning the plant root metabolome in situ for microbe‐assisted stress resistance, offering potential solutions to combat climate change. The current limitations, challenges and perspectives for engineering the plant root metabolome for modulating microbiota are collectively discussed.